Camphor induced status epilepticus: a case report - Ajeetha, Rahumath; Ramakrishnan, Anand; Sagayaraj, Benjamin (International Journal of Contemporary Pediatrics, 2018)
Camphor is very toxic compound, which can be fatal for infants and children even if ingested in very small doses. Around 3-5 ml of 20% camphor oil or >30mg/Kg is a potentially lethal dose. Camphor is used very frequently for house hold purposes. The chances of accidental ingestion by children are high particularly in toddlers. Here author report 2 years old previously well child brought with status epilepticus with no apparent trigger. Child required benzodiazipine, phenytoin and levetiracetam loading for seizure control and was ventilated. Complete evaluation for seizure cause was planned post stabilization, but during intubation camphor odour was noticed and parents accepted a possibility of camphor ingestion. Hence seizure was attributed to camphor toxicity. Further evaluation was withheld. Child had no seizure recurrence and AED was stopped prior to discharge after documenting normal neurological examination and EEG. This case highlights the need for considering camphor poisoning as a cause of status epilepticus in the toddler age group and importance of proper enquiry about possible exposure and complete examination including odour in all cases of unprovoked seizures in children which can help us avoid unnecessary investigations searching for the cause of status epilepticus.